Geospatial patterns and determinants of toddler stunting: evidence from geographically weighted regression - Muhammad Anismuslim; Henny Pramoedyo; Sri Andarini; Sudarto Sudarto (International Journal of Public Health Science (IJPHS), 2026)
This study aimed to map and analyze the spatial distribution of toddler stunting in Malang and identify key risk factors that are spatially correlated with stunting incidence across sub-districts and villages. A geospatial modeling approach using geographically weighted regression (GWR) was employed to account for local variations in the influence of risk factors, reflecting the heterogeneity of conditions that contribute to stunting in different areas. The analysis revealed significant spatial autocorrelation, with stunting cases clustering in specific locations. Results indicate that sanitation risks and household waste management practices were the most significant determinants of stunting prevalence among toddlers in Malang. Improper waste segregation, which leads to odors and attracts flies, and ineffective disposal methods, such as open burning or dumping, were strongly associated with higher stunting rates. These findings underscore the importance of targeted interventions addressing environmental health and sanitation at the local level. By integrating geospatial analysis with GWR modeling, this study highlights the spatial heterogeneity of stunting determinants, providing evidence to guide community-specific public health strategies. Improved sanitation practices and proper household waste management are critical to reducing toddler stunting in areas with clustered risk.